Kepemimpinan Visioner Kepala Sekolah dalam Meningkatkan Kinerja Guru - Nikolaus Anggal; Kristianus Kristianus; Zakeus Daeng Lio (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2019)
This research objectives to find out the teacher’s improved performance by the implementation of the School Principal’s visionary leadership at SDN 004 Busang, by comparing the Teacher’s performance before and after the implementation of the School Principal’s visionary leadership at SDN 004 Busang. This Population is the number of research subject, in this case all of the 14 Teachers or educators at SDN 004 Busang who were taken as the total sampel. The techniques used to collect data in this research using documentation research and questionnaire. Based on the responses of the respondent to the questionnaire, the School Principal’s visionary leadership score reachs 1329 and belongs to strong category with the portion of 75%. While for the improved Teacher’s performance, the hypothesis t-value test, resulted t-counted (3.66) > t-table (2.16), so that Ha is accepted and Ho is rejected, which means there were was significant improvement Teacher’s performance by on the implementation of the School Principal’s visionary leadership, and there for the hypothesis proposed in this research is proved.